The influence of personal values on consumers purchase intention for organic products. (17th February 2020) - Sandhya, G.; Nair, Gopika M.
Values lie at the core of an individual's belief system, from which attitudes and behaviours are subsequently evolved. In emerging economies, consumers are interested in protecting their environment, improving their lifestyles and living sustainably. Consumers are more conscious in making purchase decisions when it comes to health. Personal values has a major role in influencing their purchase decisions. Price is yet another factor that can moderate the decision making process among consumers. The shift in the attitude of consumers towards organic products is due to the change in the lifestyle and concern for the environmental issues. This relationship has not yet been explored in the Indian context and it is interesting to understand the consumer behaviour in a country like India. In this study, we have attempted at measuring the role of personal values on understanding the consumers' purchase intention for organic products. A descriptive research design was conducted. Samples design followed was judgmental sampling procedure. Sample size for the study was 207 respondents. The findings from the study showed evidence on personal values and price to have a significant influence on consumers intention for purchase of organic products.